Effects of β-glucan on some environmental toxins: An overview - Vetvicka, Vaclav (Biomedical papers, 2014)
Background: Beta-glucans are naturally occurring polysaccharides and constituents of the cell wall of certain pathogenic bacteria and fungi. They have proven healing and immunostimulating properties, linked to enhanced macrophage and natural killer cell function which likely involves specific interaction with several cell surface receptors, such as lactosylceramide, selected scavenger receptors, and dectin-1 (betaGR). In particular, glucan reduces the immunosuppressive effects of a number of agents including chemo therapy and radiation. More recent studies suggest a positive function for glucan in the immunosuppression caused by toxic agents in the environment.Aim: An overview of the effects of glucan on the mycotoxin, aflotoxin and other environmental toxins (mercury-thimerosal, depleted uranium).Conclusion: Glucan is effective as a natural immunomodulator and could be used as an inexpensive solution to reducing the adverse effects of some environmental toxins.
Keywords: beta-glucan; aflotoxin; mercury; depleted uranium; detoxification; immunity